EFEKTIVITAS SUPLEMENTASI BUBUK DAUN KELOR (Moringa oleifera) TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL YANG MENDERITA ANEMIA - Sylvie S. Ponomban; Rivolta Walalangi; Vera T. Harikedua (POLTEKKES KEMENKES MANADO, 2013)
Nutritional adequacy are needed by every individual since the fetus is still inthe womb, babies, children, adolescence, adulthood, to old age. Mother orexpectant mother is vulnerable group because it requires adequate nutritionshould be maintained nutritional status and health in order to give birth tohealthy babies. Poor nutrition is one of the most common nutritional disorderthat occurs during pregnancy that lead to iron deficiency anemia. Many ofthese mothers provide little iron to the fetus is needed for normal ironmetabolism, then they become iron deficiency anemia and hemoglobinlevels fell below the mother 11gr% during the third trimester. Consumption ofMoringa leaves (Moringa oleifera) is one alternative to tackling malnutrition inIndonesia. The results of modern scientific research proving that Moringaleaves are one source of plant-based foods rich in nutrients. The content ofnutrients in the leaves of Moringa is 7 times the vitamin C in oranges, 4times the vitamin A in carrots, 4 times the calcium in milk, 3 times thepotassium in bananas, 3 times the iron in spinach and 2 times the proteinfound in yogurt or protein inside an egg. This study aims to determine theincrease in hemoglobin levels in pregnant women who suffer from anemiaafter using moringa leaf powder. The design of the study is a quasiexperimental that are one group pretest-posttest design. The population ispregnant trimester II-III; Samples are pregnant trimester II-III with anemiaand total sample of 35 people. Moringa leaf powder Dosage: 2 x 2 capsulesorally daily (Moringa leaf powder contains 500 mg / capsule) was given for30 days. Examination using Hemometer Sahli.The results of the comparativehypothesis testing with Wilcoxon test between Hemoglobin levels before andafter treatment values obtained significancy 0.000 (p < 0.05), so it can beconcluded that there were significant differences between the Hemoglobinlevels before treatment and after treatment. It was concluded thatsupplementation with powdered moringa leaves (Moringa oleifera) canimprove hemoglobin levels in pregnant women suffering from anemia.